Pengembangan Penilaian Satuan Pendidikan SMP/MTs - Nurhayati Kaloko (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the development of educational unit assessment at the SMP/MTS level. This research is based on a literature study with the main data source being government regulations on educational assessment standards. As for the results of the study, it shows that this assessment has a role, among others, to help students determine learning outcomes. Based on the assessment of learning outcomes by educators, educators and students can obtain information about the weaknesses and strengths of learning and learning. To get to good quality learning, a good assessment system is needed as well. In order for the assessment to function properly, in accordance with the objectives that have been set, it is very necessary to establish an assessment standard that will become the basis and reference for teachers and education practitioners in conducting assessment activities. To achieve this, it is necessary to have good cooperation between teachers, students and schools. Keywords: Assessment, Measurement, Education, Learning Outcomes